Humeral cementless surface replacement arthroplasties of the shoulder: An experimental investigation on their initial fixation - Jakubowitz, Eike; Neubrech, Christine; Raiss, Patric; Nadorf, Jan; Tanner, Michael Christopher; Rickert, Markus; Kasten, Philip (Journal of orthopaedic research, 2011)
Cementless surface replacement arthroplasties are increasingly being used to treat arthritic humeral heads. These implants are designed to provide narrow bone resection, making a later revision easier. However, no clear evidence exists as to whether their initial fixation is sufficient for bony ingrowth. The aim of our in vitro study was to characterize the relative micromotion of two resurfacing implants with essentially different bone-facing geometries. Both systems were implanted into 10 human humeral specimens and micromotion was measured under a cyclic torque application of up to ±1.75 Nm. The mean relative rotary motion resulted in a significant difference (p = 0.036), which was attributed to design differences of central stabilizers featuring both implants. A conversion of rotary motions into relative micromotions, using recently measured moments acting on these implants during daily activities of living, nullified this difference (p = 0.088). However, depending on the shoulder load case considered, a clear difference appeared (p = 0.031-0.045). In conclusion, both resurfacing implants are capable of achieving sufficient initial fixation on the humeral head and perform relative micromotions in a range considered safe for bony ingrowth. Patient-related parameters do not appear to influence the initial fixation of these implants.
Gesehen am 04.07.2022